Antibacterial and herbicidal activity of ring-substituted 3-hydroxynaphthalene-2-carboxanilides - Kos, Jiri; Zadrazilova, Iveta; Pesko, Matus; Keltosova, Stanislava; Tengler, Jan; Gonec, Tomas; Bobal, Pavel; Kauerova, Tereza; Oravec, Michal; Kollar, Peter; Cizek, Alois; Kralova, Katarina; et al. (Molecules (Basel, Switzerland), 2013)
In this study, a series of twenty-two ring-substituted 3-hydroxy-N-phenylnaphthalene-2-carboxanilides were prepared and characterized. The compounds were tested for their activity related to inhibition of photosynthetic electron transport (PET) in spinach (Spinacia oleracea L.) chloroplasts. Primary in vitro screening of the synthesized compounds was also performed against four Staphylococcus strains and against two mycobacterial species. 3-Hydroxy-N-(2-methoxyphenyl)naphthalene-2-carboxamide showed high biological activity (MIC = 55.0 µmol/L) against S. aureus as well as methicillin-resistant strains. N-(2-Fluorophenyl)-3-hydroxynaphthalene-2-carboxamide showed higher activity (MIC = 28.4 µmol/L) against M. marinum than the standard isoniazid and 3-hydroxy-N-(4-nitrophenyl)naphthalene-2-carboxamide expressed higher activity (MIC = 13.0 µmol/L) against M. kansasii than the standard isoniazid. Cytotoxicity assay of effective antimicrobial compounds was performed using the human monocytic leukemia THP-1 cell line. The PET-inhibiting activity expressed by IC50 value of the most active compound 3-hydroxy-N-(3-nitrophenyl)naphthalene-2-carboxamide was 16.9 μmol/L. The structure-activity relationships of all compounds are discussed.
Keywords: Hydrazines; fotosyntéza; Staphylococcus aureus; chloroplasty; Structure-Activity Relationship; Photosynthesis; antibakteriální látky; Microbial Sensitivity Tests; transport elektronů; Chloroplasts; Spinacia oleracea; Herbicides; vztahy mezi strukturou a aktivitou; Electron Transport; lidé; hydraziny; Anti-Bacterial Agents; Humans; mikrobiální testy citlivosti; herbicidy